Effect of Ethylenediamine-N, N′-disuccinic acid (EDDS) on the speciation and bioavailability of Fe2+ in the presence of sulfide in anaerobic digestion. (April 2017) - Thanh, Pham Minh; Ketheesan, Balachandran; Yan, Zhou; Stuckey, David
Highlights: Speciation and bioavailability of Fe 2+ was determined at steady state conditions. Sulfide precipitated Fe 2+ as FeS and hence reduced the performance of the SAMBR. EDDS was able to compete with sulfide and improve Fe 2+ bioavailability in a SAMBR. Abstract: The effects of a biodegradable chelating agent, Ethylenediamine-N, N′-disuccinic acid (EDDS), on the speciation and bioavailability of iron (Fe 2+ ) in anaerobic digestion were examined. Fe 2+ supplementation at 10 mg/L increased methane yield, but the presence of 8 mg/L sulfide led to the precipitation of Fe 2+ as FeS which limited its bioavailability. The results confirmed that the EDDS could replace common chelating agents with low biodegradability (EDTA and NTA), and improve the bioavailability of Fe 2+ by forming an Fe-EDDS complex, thereby protecting Fe 2+ from sulfide precipitation. Experimental findings from sequential extraction using the Community Bureau of Reference (BCR) method, and quantification of free EDDS and Fe-EDDS complex using UHPLC, confirmed that 29.82% of Fe 2+ was present in bioavailable forms, i.e. soluble and exchangeable, when EDDS was added at 1:1 molar ratio to Fe 2+ . As a result, the methane production rate increased by 11.17%, and the methane yield increased by 13.25%.